PENGARUH KOMUNIKASI INTERPERSONAL KEPALA BIDANG TERHADAP TINGKAT STRES KERJA PEGAWAI (Jurnal Tata Kelola Pendidikan, 2019)
Background research on the problem of how much influence the head of the fieldinterpersonal communication has on the level of work stress of employees in the field ofSenior High School Development at the Education Office of West Java Province. Theresearch method used is a descriptive method supported by literature study. The techniquecarried out in this study consists of two stages. In the early stages, questionnaires weredistributed via Google Form to the West Java Provincial Education Office in the PSMASector, the second was to test the validity and reliability tests, and data analysis while thetotal population of this study was 37 people, and the number of samples was the same asthe population because it used the technique. total sampling. Based on the results of dataprocessing calculated using the Weight Means Scores (WMS) technique, it shows that thegeneral trend for variable X (Interpersonal Communication) is 4.33 and is in the very goodcategory. Meanwhile, the average general trend for variable Y (Job Stress) is 4.22 whichis in the very good category. The results of the calculation of the normality test of thedistribution show that the X and Y variables are normally distributed. Judging from thecalculation of the correlation coefficient (Tcount) using the Perason Product Momentformula, the correlation coefficient value is 0.402. This shows that there is a strong enoughrelationship between the Y variable. The results of the significant test with the t-test showthat the t-test is 2,595 and it is known that the t-table is 1.689 when compared, then tcount>ttable. To determine the influence of variable X and variable Y is shown from thecalculation of the analysis of the coefficient of determination (KD) of 16.1%. Based on theresults of the above research, it can be concluded that the research hypothesis is that thereis a positive and significant influence between the Head of Field InterpersonalCommunication on the Work Stress Level of Employees in the Field of Senior High SchoolDevelopment at the Education Office of West Java Province. The results of this study areexpected to provide a benefit both for institutions, employees and for future researcherswho will examine communication problems on the level of work stress.
Keywords: Interpersonal Communication; Job Stress